Stevia rebaudiana Bertoni M. Under Stress Condition: An Environmental Case - Dian Pratama Putra; Prasanto Bimantio; Amallia Ferhat; Nanda Satya Nugraha (Politeknik LPP Yogyakarta, Indonesia, 2021)
The importance of sugar makes every household life must have these sweeteners to meet daily needs. Stevia has several advantages including the level of sweetness that reaches 100-200 the sweetness of sugar cane and low calorie so safe to be consumed by diabetics and obesity. The possibilities of plants to grow on soil properties and fertility become an important issue in agricultural cultivation systems. In the case study conducted, this study looked at 4 behaviors that characterize the relationship between soil and Stevia, the relation was: (1) the condition of the soil and plants when water is lacking, (2) the condition of plants lacking nutrients, (3) differences in the type of soil and (4) conditions that contradict the growing conditions of Stevia. Data taken included: soil moisture content, soil NPK element content, plant and soil appearance descriptively and plant stevioxide content under stress conditions. The result stevia under stress conditions must be watered as much as 250 ml/day if below that the plant will wither in 1 week and if more than that the plant will experience root rot. Stevia which lacks nutrition when under stress will flower 1 month faster than usual, a condition where there are nutrients but high temperatures will trigger the wilt of stevia stems even though it has been watered 250 ml/day. This study also looked at the reaction of plants to different types of soil, where soils with more Stevia clay texture produce more leaves than those planted on sandy-textured soils.Â